Israeli Market Needs for Arabic Translations - Robinson, Abraham (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1998)
AbstractThis article looks at the growing need for Arabic translations in Israel. It comments on the areas of need, safeguards required and the attempts at translator training.